OPTIMALISASI KEGIATAN FIRE DRILL GUNA MENINGKATKAN KESIAGAAN CREW DI KAPAL SPOB SEROJA XVIII - Raul Francisko Idris; Bayu Yudho Baskoro; Rizal Rochmansyah; M. Kurniawan; Yusuf Pria Utama (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Fire is one of the risks that can occur anytime and anywhere in marine shipping activities, the risk of fire on ships is quite large because the number of fire cases ranks second after the number of ship sinking cases. Management must pay attention to the provisions stipulated in the work safety regulations on ships as regulated in SOLAS (Safety of Life at Sea), ISM Code (International Safety Management Code) and STCW (Standard of Training, Certificate and Wachtkeeping for Seafarers) conventions to protect seafarers and prevent the risks in carrying out an activity on board. The purpose of this study was to find out how to implement Fire Drill as an effort to increase crew alertness on the Seroja XVIII. Limin Ventures. In this scientific work, the author uses a qualitative descriptive approach and primary and secondary data sources. The results of this study can be seen that the application of procedures before the Fire Drill or fire drills have been implemented well on the Seroja XVIII by holding a safety meeting before the activity and the captain always asks each crew about their duties and responsibilities in the event of a fire on board.